Hedgehog-like spin texture in Sb-doped MnBi_{2}Te_{4} - Meng Zeng; Shu Mo; Ke Zhang; Yu-Jie Hao; Yu-Peng Zhu; Xiang-Rui Liu; Cheng Zhang; Ming-Yuan Zhu; Shiv Kumar; Takuma Iwata; Koji Miyamoto; Taichi Okuda; et al. (Physical Review Research)
We employ spin- and angle-resolved photoemission spectroscopy and circular-dichroism angle-resolved photoemission spectroscopy to systematically investigate the spin texture of Sb-doped MnBi_{2}Te_{4}. Our results display a hedgehog-like spin texture in this system which is signified by reversed-orienting out-of-plane spins at the Dirac gap. Our finding reveals the presence of time-reversal symmetry breaking, implying the possibility for realization of the high-temperature quantum anomalous Hall effect.